Improvement of strength capacities of middle-distance runners as the major factor of achieving high sports results at the stage of maximal realization of individual capabilities - V.I. Bobrovnik; Y.P. Tykhonenko (Physical Education of Students)
Purpose : the formation of a specific group exercises power orientation. Material : the study analyzes scientific and methodical literature, best practices. An analysis of the diaries of qualified middle distance runners. Results : group exercises designed to develop strength abilities (maximum, explosive strength, strength endurance) and methods of their use in the annual training cycle. To develop maximum force applied athletes exercise with weights (95-100% of the maximum mass). Recommended special exercises the running and hopping character with weights of 15-20 %, with which the athlete can get from a sedan. Group of exercises should be used in a specially - preparatory period of the annual cycle phase maximum realization of individual opportunities. Conclusions : the developed specific group of exercises that in different periods of year-long preparation for the implementation phase of the maximum individual empowerment contributes to the maintenance and implementation of power abilities of athletes.